La Dinámica Cultural Y La Prevención De Riesgos De La Población Tumba San Francisco – Quimiag, Provincia De Chimborazo. Su Resiliencia Ante Fenómenos Adversos En El Año 2010 – 2011 - Zambrano, Ginno Sidney Jarrín; Santillán, Carlos Arturo Jara (European Scientific Journal, ESJ, 2017)
This research exposes the process that took place in the Tumba San Francisco community, Chimborazo – Ecuador. It is used for the prevention of risks and response to adverse events. Also, it increases the resilience of its inhabitants between the periods of 2010 – 2011. By fulfilling the first specific targets which was performed, the socioeconomic diagnosis of Tumba community, the methodology was proposed by the authors. It gives priority to the active participation of the habitants. This study aims to work with 100% of the population of the universe through the application of surveys, interviews, population census, and workshops. In the second objective, training workshops were held based on the concepts and management of hazards, threats, vulnerability, risks, and disasters. This, however, was accomplished through the methodology proposed in the Project “Sinchi Runa” (Strong Man) by the European Commission and CARE KNH Ecuador of the DIPECHO VI program for Latin America. Also, it was applied in other communities and parishes of the Riobamba canton. In achieving the third and final goal, the process and project of translation or relocation of the population was elaborated. It is aimed at improving their resilience to natural disasters (landslide). To foster the development of this objective, a profile of projects was elaborated under the methodology of SENPLADES (2011). Finally, 100% of the study universe was successfully transferred, thus fulfilling the main objective of the research, maintaining its cultural dynamics, and improving its capacity of resilience through the methodological processes of the research.